Identifying geodesic acoustic modes in WEST tokamak plasmas - Soh, Kerwin Chuen Han (Nanyang Technological University, 2024)
Fusion energy represents a promising source of energy for humankind, a method to harness the same clean and limitless power of the sun without the negative impacts of climate change. Geodesic Acoustic Modes (GAMs) are axisymmetric oscillations of the plasma's radial electric field, with poloidal flow variations. GAMs oscillate at a frequency linked to the plasma sound speed and the magnetic field geometry, mediating the transfer of energy between turbulent eddies and ZFs. GAMs influence the overall stability and confinement efficiency of the plasma, promoting a homogeneous and stable plasma state. GAMs are ubiquitous in toroidal MCF devices, and are studied widely, either theoretically, experimentally, or numerically. While numerous papers have investigated into the interactions between GAMs and turbulence, these complex mechanisms have not been completely understood yet. This study employs the use of Doppler back-scattering diagnostics alongside multiple signal classification algorithms, to analysis and identify the presence of GAMs in the Tungsten (W) Environment in Steady-state Tokamak (WEST). During the analysis of GAMs, an anomaly was observed in a plasma discharge. The discharge exhibited two peaks in the GAM amplitude profile, which goes against theoretical expectations and experimental observations. This study investigates the “double-bump” phenomenon and formulates a new equation in the process to describe the unique phenomenon. Through the findings of the report, additional research can be done to refine the equation and expand our comprehension of GAMs mechanics in fusion plasmas.